Worshipping ceremony of the Mah Meri aboriginal tribe - Malaysia. Jabatan Muzium dan Antikuiti (Kuala Lumpur : Jabatan Muzium dan Antikuiti)
This documentary features the act of worshipping at the beach by the Mah Meri community in Kampung Sungai Judah, Carey Island, Banting. This tradition is held annually to acknowledge the Moyang Getah or Metah regarded as sacred
Title from title screen
VCD format
Keywords: Mah-Meri (Malaysian people) -- Social life and customs; Mah-Meri (Malaysian people) -- Religion; Mah-Meri (Malaysian people) -- Medicine